INTEGRATED NEUTROSOPHIC DEMATEL, TOPSIS, AND GRA APPROACH FOR FINANCIAL RATIO PERFORMANCE EVALUATION OF NASDAQ EXCHANGE - Venugopal, Ramalingam; Veeramani, Chinnadurai; Das, Amrit (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Accounting and economic-based financial metrics play a crucial role in-stock selection or stock ranking by providing objective and quantifiable measures of a company's financial health and performance. These metrics are used by investors, analysts, and portfolio managers to assess the potential risks and returns associated with investing in a particular stock. This study aims to contribute to stock selection and ranking methodologies by proposing a novel Multi-Criteria Decision-Making (MCDM) model. The model integrates the Decision-Making Trial and Evaluation Laboratory (DEMATEL), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and Grey Relational Analysis (GRA) approaches within a neutrosophic environment. Focusing on companies listed on the NASDAQ stock exchange, the research evaluates financial metrics from June 2018 to May 2022, specifically in the Information Technology sector across eight industries. The financial metrics are categorized into two groups: accounting-based financial measures (AFM) and economic value-based financial measures (EFM). Two experts assess the data, and the neutrosophic DEMATEL approach is employed to calculate the weights of the criteria. Subsequently, companies are ranked using neutrosophic TOPSIS and GRA methods. In conclusion, the study conducts a sensitivity analysis using the neutrosophic GRA method to validate the efficiency of the ranking. This research significantly contributes to the field by introducing a comprehensive MCDM model that amalgamates various decision-making techniques within a neutrosophic framework. The results not only provide valuable insights into stock ranking on the NASDAQ stock exchange but also demonstrate the efficacy of the proposed methodology. The integration of DEMATEL, TOPSIS, and GRA in a neutrosophic environment adds originality to the existing literature on financial metrics and MCDM models in stock selection.